2019
DOI: 10.1089/can.2018.0020
|View full text |Cite
|
Sign up to set email alerts
|

Reduction of Benzodiazepine Use in Patients Prescribed Medical Cannabis

Abstract: Background: Benzodiazepines are a class of medication with sedative properties, commonly used for anxiety and other neurological conditions. These medications are associated with several well-known adverse effects. This observational study aims to investigate the reduction of benzodiazepine use in patients using prescribed medical cannabis.Methods: A retrospective analysis was performed on a cohort of 146 medical cannabis patients (average age 47 years, 61% female, 54% reporting prior use of cannabis) who repo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
27
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
3
3

Relationship

0
10

Authors

Journals

citations
Cited by 38 publications
(31 citation statements)
references
References 19 publications
2
27
2
Order By: Relevance
“…The positive bi-directional association between benzodiazepines and analgesics is supported by many previous studies ( 37 39 ). However, others have found a negative association between the use of cannabis and benzodiazepines ( 40 , 41 ), and have identified a substitutional role between them ( 42 ). These findings could explain the negative bi-directional relationship found in the present study.…”
Section: Discussionmentioning
confidence: 99%
“…The positive bi-directional association between benzodiazepines and analgesics is supported by many previous studies ( 37 39 ). However, others have found a negative association between the use of cannabis and benzodiazepines ( 40 , 41 ), and have identified a substitutional role between them ( 42 ). These findings could explain the negative bi-directional relationship found in the present study.…”
Section: Discussionmentioning
confidence: 99%
“…Further, Rogers et al (2019)(2) stated that potential polysubstance use of other illegal substances taken for the treatment of pain -was a signi cant limitation for fully understanding the cannabis-opioid relationship. Likewise, there are a limited number of Canadian-speci c epidemiological studies (6,52,53) that study medical cannabis -and even smaller numbers that study its association with opioid use (6,29). The majority of these studies have very small cohort numbers and are highly reliant on self-reported outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…There is also evidence that prescribing cannabinoid-based medicines may reduce the use of benzodiazepines and non-steroidal anti-inflammatory drugs. 52 , 64 , 126 …”
Section: Potential As Adjunctive Therapymentioning
confidence: 99%